Pendidikan Kesehatan tentang Anemia pada Remaja Putri di SMA N 12 Kabupaten Merangin - Dini Junita; Arnati Wulansari (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
Anemia is the impact of nutritional problems on teenager girl. Nutritional anemia is caused by a lack of nutrients that play a role in the formation of hemoglobin, it can be due to lack of consumption or absorption disorders. Only 62% of anemia mothers have received iron supplemented tablets in the working area of Puskesmas Simpang Limbur, while the iron supplemented tablet program for teenager girls in high school has not been implemented. The purpose of this community service activity is to provide information and motivation to teenagers to prevent anemia. Providing information in the form of health education regarding the definition, signs, clinical signs and symptoms and the impact of anemia. The implementation method is in the form of counseling, discussion, practice simulation and pre-post test evaluation. Monitoring evaluation is carried out by looking at the indicators of success in the aspect of target attendance attending every meeting in service and practice activities to the target, reflections and feedback from the participants. The results of the activity show that school support is very good, students' knowledge of anemia is more than 80%. The material still needs to be improved regarding the risk factors for anemia in adolescents. Collaboration with health workers is needed to gain new knowledge on a regular basis, as well as empowering students as youth cadres.